Altered Directed Functional Connectivity of the Hippocampus in Mild Cognitive Impairment and Alzheimer’s Disease: A Resting-State fMRI Study - Xue, Jiayue; Guo, Hao; Gao, Yuan; Wang, Xin; Cui, Huifang; Chen, Zeci; Wang, Bin; Xiang, Jie (Frontiers in Aging Neuroscience, 2019)
The hippocampus is generally reported as one of the most important regions in Alzheimer’s disease (AD) and is closely associated with memory function and orientation. Undirected functional connectivity alterations occur in patients with mild cognitive impairment (MCI), and AD has been the subject of much investigation. However, the abnormal patterns underlying directed functional connectivity remain poorly understood. In this work, to identify the changes in directed functional connectivity between the hippocampus and other brain regions, Granger causality analysis (GCA) based on voxels was applied to resting-state functional magnetic resonance imaging (rs-fMRI) data from 29 AD, 65 MCI and 30 normal control (NC) subjects. The results show significant differences in directed functional connectivity patterns among the three groups. Compared with the NC group, brain regions showing changes in directed functional connectivity with the hippocampus were few and mainly included the temporal lobe, frontal lobe and cingulate cortex in the MCI group. However, abnormal directed connectivity in the AD group was obviously larger in terms of the number or size of the voxels and was more widely distributed. Most of the abnormal connections were unidirectional and were asymmetric in the two hemispheres. The findings of this study reveal abnormalities in the hippocampus of MCI and AD patients in transmitting and receiving information and offers insight into the neurophysiological mechanisms underlying MCI and AD.